Pengaruh mengonsumsi madu Aceh Selatan terhadap tingkat keasaman pH Saliva pada murid Sekolah Dasar - Cut Ratna Keumala; Sisca Mardelita; Andriani Andriani; Intan Rahayu (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Saliva is an oral fluid secreted by the salivary glands.  Saliva plays a role in preventing dental and oral diseases, one of the things that must be considered is the degree of acidity (pH) of saliva. At normal pH, saliva functions to reduce bacterial growth, help the growth of epithelial skin cells, reduce plaque accumulation and activate enzyme work. One of the actions to maintain salivary pH is by using honey.Objectives: to determine the effect of honey on the acidity level of salivary pH of children in grades IV and V at Lampeuneurut State Elementary School.Methods: The study was conducted at Lampeuneurut State Elementary School in February 2022. The research design is quasi-experiment. The sample size was 53 students. Data collection through interviews and observations and measurement of salivary pH. Intervention was carried out by providing South Aceh honey for one week. Data analysis using T-test.Results: There is a decrease in salivary pH in Lampeuneurut State Elementary School children who are given honey before and after (p = 0,0001). Before being given honey, the average or mean value obtained was 6,58, while after being given honey, the mean value of salivary pH in Lampeuneurut State Elementary School children in Aceh Besar Regency dropped to 5,21 and made the salivary pH decrease to acid.Conclusion: There is an effect of consuming honey on the acidity level of salivary pH of class IV and V children at SDN Lampeuneurut. Consuming honey and maintaining dental health can also increase endurance to maintain health, especially in the teeth and mouth.